Look what you made me do laboratory experiments explaining human behavior in non-solitary contexts - Capuno, Jose Reuben; Ong, Melson
Inspired by Rotter’s prediction formula, this paper proposes a concise model for explaining human behavior in non-solitary situations, where responses carry economic consequences. An experiment was conducted wherein participants, either alone or in groups, were presented with free money and chocolates and given two minutes to decide whether or not to take them. Participants were then asked to answer questionnaires designed to reveal the motivations behind their decisions. Their reported motivations were classified into four Motivational Dimensions: Self-State, Grand-State, Self-Ideal, and Grand-Ideal. These four comprise the total degree of motivation for a decision, called the Reinforcement Value, which, when multiplied by probability of a consequence, yields Expected Value. The latter is taken as analogous to Expected Utility in traditional economics. To determine which Dimension most strongly motivates participants, the number of motivations per dimension was then regressed against amounts taken. Results show that over half did not take free goods, but for those who did, the Self-State, representing concrete benefits limited to the self, is the strongest predictor of the decision to take either type of free goods, regardless of whether or not participants are in groups. This study addresses the gap in behavioral economics where deviations from homo economicus projections are interpreted post hoc and speculatively.